Rate of Epstein-Barr Virus in Gastric Adenocarcinoma in Egyptian Patients in View of the WHO Classification and Correlation with p16 Immunoreactivity - Samir, Safia; Ahmed, Hend Okasha; Diab, Tarek M.; Mostafa, Amr; Elmeligy, Hesham A.; Kamel, Amira; Khalil, Heba (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND AND AIM: Gastric cancer (GC) is one of the top causes of cancer-related deaths worldwide. According to the Cancer Genome Atlas, there are four subtypes of GC, with the Epstein-Barr virus (EBV) subtype accounting for about 10% of cases. EBV infection causes EBV-associated GC (EBVaGC). The previous research suggested that the presence of the EBV viral genome in gastric carcinomas could be used as a surrogate marker for targeted therapy and optimal GC treatment. AIM: We aimed to explore the rate of EBV involvement in gastric carcinogenesis from molecular perspective view and to evaluate the role of the tumor-suppressor protein p16 as a marker for diagnosis in GC Egyptian patients in relation to EBV infection. METHODS: One hundred-four surgically resected GC cases were analyzed. Two methods including quantitative real-time polymerase chain reaction (qPCR) for detecting EBV-derived latent membrane protein-1 (LMP-1) and Epstein-Barr nuclear antigen-1 (EBNA-1) genes as well as immunohistochemistry (IHC) detection of LMP-1 protein and p16 protein on paraffinized tissue blocks were applied. RESULTS: Using IHC, p16 protein was presented in 90/104 (86.5%) of the GC cases, and EBV LMP-1 was detected in 4 cases (3.84%). qPCR detected 14 cases positive for EBV (13.46%). In EBV positive cases detected using qPCR, no expression of p16 was detected. CONCLUSION: EBVaGC has a low incidence in Egypt; loss of p16 expression was recognized in EBVaGC and could be considered as a promising biomarker of EBVaGC. The combination of the two methods IHC and qPCR in addition to p16 is recommended for improving the accuracy of identification of infected cancer.